The Survival and Growth Rates of Transplanted Ornamental Coral Reefs In Pramuka Resort of Seribu Islands - Mustahal Mustahal; Nur Rahmawaty (JURNAL PERIKANAN DAN KELAUTAN, 2011)
The highly demand of coral reefs trading in various countries, have endangered to the coral reef condition in Indonesia. Many people exploited the coral reef bed to yield part of their needs of incomes. Therefore, serious conservation efforts are urgently needed. In this relation a study have been carried out to observe the survival and growth rate of transplanted coral reefs in Pramuka resort of Seribu Islands. In this study four species of coral reefs were used as the experimental objects which were transplanted into cemented substrates. They were, namely Acropora formosa, Hydronopora rigida, Pocilopora eydousi, and Seriatopora hystrix. The fragment of these coral were measured every month for their length and survival. The results showed that survival rate were ranged from 89.06 to 100% and the length gained were varied after 5 month transplantation from 6.4 cm for Acropora formosa (highest) and 0.74 cm for Hydronopora rigida. (lowest)